Cognitive Development Through Language Learning: Examining Bilingualism in Early Childhood Education - Shani, S.S.; Begum, Feroz; Paipuru, Sudha; Haseena, S.; Subramanyam, V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: This study investigates the cognitive and linguistic advantages of bilingualism in early childhood education, focusing on language proficiency and executive function (EF) in bilingual and monolingual children. Prior research has suggested the potential benefits of bilingualism in cognitive flexibility, language development, and social skills, which are critical for educational success. Method: The study assessed the language skills and cognitive flexibility of 100 preschool-age children using standardized assessments, including the Peabody Picture Vocabulary Test (PPVT) for language skills and the Dimensional Change Card Sort (DCCS) for cognitive flexibility. The children were divided into bilingual and monolingual groups to compare performance on these assessments. Result: Bilingual children demonstrated higher scores in native language proficiency (M = 95.6) and executive function (M = 89.2%) than monolingual children, indicating superior language and cognitive flexibility. These findings suggest that bilingualism enhances flexibility, consciousness, problem-solving, social skills, and emotional regulation in young children. Conclusion: The results support the inclusion of bilingual education in early childhood programs to foster language development and cognitive skills in young children. However, the study’s limitations, including a narrow sample and reliance on standardized assessments, highlight the need for further research across diverse populations to explore the long-term effects of bilingualism. The cognitive, language, and social advantages observed are likely beneficial for future academic success and life skills.